活性氧清除剂衍生物的制备及用途 (2022)
式(I)a或(I)b的化合物：包括某些醌衍生物，以及相应的药物组合物，其可以用于调节受试者的铁死亡。本文还公开了这些化合物和药物组合物的制备以及它们在制造药物中的潜在用途，所述药物用于减少细胞中的活性氧(ROS)以及用于预防、治疗、改善某些相关的病症或疾病。 Compounds of Formula (I)a or (I)b:including certain quinone derivatives, and the corresponding pharmaceutical compositions, which may serve to modulate ferroptosis in a subject. Also disclosed herein are the preparations of these compounds and pharmaceutical compositions and their potential uses in the manufacture of a medicament in reducing reactive oxygen species (ROS) in a cell and for preventing, treating, ameliorating certain related disorder or a disease.